Genomic identification of expressed globulin storage proteins in oat - Gil-González, Aina Belén; Sjögren, Lars L. E.; Bernfur, Katja; Olsson, Olof; Zambrano, Jose Alfredo (Frontiers in Plant Science, 2024)
Introduction: Oats, a highly nutritious cereal known for their health benefits, contain various macromolecules of significant biological value, including abundant and highly digestible proteins. Despite their importance, oat proteins have not been extensively studied. Here, we present a complete set of the expressed globulins genes, which code for the main storage protein in oats as well as their chromosomal positions. Methods: Published expressed sequence tags for globulins were used as queries in the Sang oat genome. In addition, globulin proteins were fractionated from oat flour by solvent extraction based on differential solubility with other classes of cereal proteins. The protein fractions were separated by gel electrophoresis and analyzed by tandem mass spectrometry to confirm their identity and expression in seed. Results and discussion: In total 32 globulin gene sequences were identified on the oat genome. Out of these, the expression on RNA level could be confirmed and 27 were also detected as expressed proteins by MS. Our results provide the most extensive set of salt-soluble oat globulin sequences to date, paving the way for further understanding their implications for human nutrition. In addition, a simple methodology to fractionate oat proteins is presented.